PID tuning method of process control / Wan Azwar Hakimi Wan Azeman - Wan Azeman, Wan Azwar Hakimi (2024)
PID tuning performance using the Cohen Coon and Chien Hrones Reswick methods has been studied in liquid flow process control. The study begins with an open-loop test in order to determine some of the essential system parameters, namely dead time and time constant, from which P, PI, and PID tuning values for both methods are calculated. Stability, overshoot, settling time, and disturbance rejection will be the criteria to analyze the system response and find the most effective approach to tune it.